THE EFFECT OF ELEVENIA TELEVISION ADVERTISEMENTS ON STUDENTS’ BUYING INTEREST - Wiana, Rama Dwissa; Permana, Dwika Lutfhi; Kennedy, Janeru (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2021)
The presence of television advertisements certainly causes a significant shock to the Indonesian advertising media landscape.The effective impact of repeated advertising exposure is to gain the attention and experience of the individual recipients who are exposed to the advertising message, and openly accept the messages they convey. In addition to paying attention to the wants and needs of its consumers, Elevenia also always introduces and instills an image for consumers of its brand by using various advertisements including television advertising media. The purpose of this study was to find out how much influence the variable "Elevenia Television Advertising Exposure" had on "Student Buying Interest". The theory in this study is the Theory of Individual Differences.This theory examines differences - differences between individuals as targets of mass media when they are exposed, thus causing certain effects. The method used in this study is Quantitative with an Explanatory approach.The population in this study is the number of Untirta Communication Science Students Class of 2012, which is 106 students. The determination of sample size in this study used the Yamane formula, based on an error rate of 10%, so that the sample of respondents in this study was 51 samples of respondents. Meanwhile, the sampling technique used is Proportionate Stratified Random Sampling.The results showed that the Elenia Television Ad Exposure produced a percentage value of 72.2%. Meanwhile, Student Buying Interest generates a percentage value of 70%. From the results of the correlation analysis test, it can be explained that the relationship between the variables "Advertising Exposure" and "Buying Interest" is 0.566. This suggests that the relationship between the two variables is of Medium value, as it is at a correlation interval of 0.40 - 0.599 as listed in table 3.11 of the Correlation Coefficient Interval. The result of the value of the coefficient of determination of the variable "Elevenia Television Advertising Exposure" to the variable "Buying Interest" is 0.513, then 26.31% of students’ buying interest is the contribution of the advertising exposure variable, while the remaining 73.69% can be explained by other causes. With the results described in this study, that the calculated value (4.185) >ttabel (1.677). The figure shows that Ho was rejected and Ha was accepted